2017
DOI: 10.1093/ehjci/jex007
|View full text |Cite
|
Sign up to set email alerts
|

Tissue characterization by T1 and T2 mapping cardiovascular magnetic resonance imaging to monitor myocardial inflammation in healing myocarditis

Abstract: Healing of myocarditis can be monitored by native myocardial T1 and T2 measurements without the need for contrast media. Both native myocardial T1 and T2 provide an excellent performance for assessing the stage of myocarditis by CMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 30 publications
6
67
1
Order By: Relevance
“…One previous study had demonstrated that in cases with coexisting inflammation and diffuse fibrosis, the ECV would reflect the sum of both pathologies [31]. ECV has shown excellent discriminative value in differentiating myocarditis patients from healthy subjects [21,32], and declined significantly with the recovery of myocarditis [21]. In our study, myocardial ECV provided good discriminative value between newly diagnosed IIM patients and normal controls, with a significant decrease in the ECV of both the myocardium and skeletal muscle at follow-up CMR.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study had demonstrated that in cases with coexisting inflammation and diffuse fibrosis, the ECV would reflect the sum of both pathologies [31]. ECV has shown excellent discriminative value in differentiating myocarditis patients from healthy subjects [21,32], and declined significantly with the recovery of myocarditis [21]. In our study, myocardial ECV provided good discriminative value between newly diagnosed IIM patients and normal controls, with a significant decrease in the ECV of both the myocardium and skeletal muscle at follow-up CMR.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Hinojar et al found that lupus myocarditis patients had elevated myocardial native T1 and T2 relaxation times and showed a significant decrease after intensive therapy, which suggests an attenuation of myocardial inflammation [20]. Bohnen et al found that native myocardial T1 and T2 measurements provide excellent performance for monitoring the healing of myocarditis with a significant decline based on the stage of acute myocarditis [21]. Spieker et al also found T2 mapping to be a good tool for monitoring myocardial inflammation in patients with suspected acute myocarditis [22].…”
Section: Abbreviationsmentioning
confidence: 99%
“…In recognition of CMR as the current primary diagnostic tool for the assessment of suspected acute myocarditis, the CMR‐based imaging Lake Louise consensus criteria were developed in 2009 . Initially, the criteria were based on imaging findings seen on conventional T 2 ‐weighted sequences, early gadolinium enhancement pattern and LGE and several studies have shown that it is extremely useful for assessment in both the diagnosis and recovery of patients with myocarditis without the need for contrast administration . Although LGE can persist in those with decreasing inflammation, native T 1 mapping normalizes as the myocardium recovers and can differentiate between those with active inflammation vs. healed disease .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…For this type of analysis, more advanced CMRI features such as T1 and T2 mapping will be necessary. 39,41 On the basis of our data, a CMRI without routine T1 and T2 mapping that does not reveal the presence of inflammation does not justify the decision not to perform an EMB.…”
Section: Discussionmentioning
confidence: 84%
“…It will be interesting to evaluate the correlation between the biopsy and the CMRI findings in more detail and to find out how sensitive CMRI really is when it comes to chronic inflammation or viral persistence. For this type of analysis, more advanced CMRI features such as T1 and T2 mapping will be necessary . On the basis of our data, a CMRI without routine T1 and T2 mapping that does not reveal the presence of inflammation does not justify the decision not to perform an EMB.…”
Section: Discussionmentioning
confidence: 89%